Efficacy of infliximab on MRI-determined bone oedema in psoriatic arthritis. Issue 6 (21st December 2006) - Marzo-Ortega, Helena; McGonagle, Dennis; Rhodes, Laura A; Lyn Tan, Ai; Conaghan, Philip G; O'Connor, Philip; Tanner, Steven F; Fraser, Alexander; Veale, Douglas; Emery, Paul
Abstract : Background: Psoriatic arthritis (PsA) is commonly associated with bone pathology, including entheseal new bone formation and osteolysis. On MRI, areas of active clinical involvement are represented by bone oedema and synovitis. Aim: To assess the impact of infliximab on bone oedema in PsA as shown by MRI. Methods: 18 patients with joint swelling, psoriasis and seronegativity for rheumatoid factor received four infusions of infliximab, 3 mg/kg, in combination with methotrexate. MRI of the affected hand (12 patients) or knee joints (6 patients) was performed before and after treatment. The primary outcome was the assessment of bone oedema and synovitis at 20 weeks as shown by MRI. Secondary outcomes included the American College of Rheumatology (ACR) response criteria, psoriasis skin scores (Psoriasis Area and Severity Index (PASI)) and a quality of life measure (Psoriatic Arthritis Quality of Life (PsAQoL)). Results: At baseline, bone oedema was seen in 50% of patients (seven hands and two knees) in 30% of scanned joints, and this improved or resolved in all cases in the hand joints (p = 0.018) and in one knee joint at 20 weeks. Synovitis was found to be reduced in 90% of cases on MRI. Likewise, a significant improvement in all clinical outcomes, including PASI (p = 0.003) and PsAQoL (p = 0.006) was seen at week 20. 65% (n = 11) of the patients achieved an ACR response, of whom 45% had ACR70 or above and 54% had ACR20 or ACR50. Conclusions: Infliximab treatment is associated with dramatic improvements in MRI-determined bone oedema in PsA in the short term. It remains to be determined whether infliiximib treatment is the cause for prevention of new bone formation, bone fusion or osteolysis in PsA as shown by radiography.